Simulation of genetic populations with biochemical properties: II. Selection of crossover probabilities - Rosenberg, Richard S. (Mathematical biosciences, 1970)
A previous article [1] presents a simulation model for modeling complex interactions between a dynamic population and its environment. In that article alleles are represented by an ordered pair ( a i , x i ) where the first member a i defines an enzyme (or enzymes) and the second member x i defines a “linkage” factor. In the present article, this model is used to study the process of selection on the crossover probabilities in a small population. It is found that strong selective forces are necessary to drive such a population. These include the possibility of a relatively large number of offspring for a given mating and broad mortality procedures. They are necessary in the face of the stochastic effects to which a small population is subject.